Rural Consumer Behavior towards Elite Atta - P.N. Keerthi and Divya Vijayan
Small scale industries in food sector are growing day by day. Each and every company has to compete with multinational company so hardly for their survival. The success of any organization depends upon the level of acceptance it gains among its consumers. It is imperative that consumer behavior is essential to devise future strategies and to gain advantage in the market. It is in this backdrop the study aimed to delineating the consumer behavior of Elite Atta as perceived by its consumers. The study was based on primary and secondary data. Primary data were collected through the survey method using structured questionnaire. A Sample of 100 customers of Atta were selected conveniently for the field survey. The study is confined to Ayalur area of Nenmara, Thrissur only. Percentage analysis and satisfaction index were the main tools used for analysis. The study found out that the consumers are satisfied with the availability of the Elite Atta but they are not satisfied with the availability the product. The study suggested that Elite has to give more importance to their promotional activities.